ICRI White Paper: An Update on Role of Conventional Radiography in Imaging of Pediatric Gastrointestinal Tract - Jain, Sanjay N.; Shah, Rushit S.; Modi, Tanvi; Varma, Ravi U. (Indian Journal of Radiology and Imaging, 2022)
Plain abdominal radiographs and gastrointestinal contrast studies remain the first line of investigation for the evaluation of several conditions due to their easy availability and ease of use in pediatric patients. A systematic approach to evaluating the plain radiograph for pediatric abdomen can lead the radiologist to a relevant differential diagnosis in most cases. In other cases, it leads the radiologist to the next line of investigation. The plain radiograph of the abdomen is requested for several conditions ranging from abdominal pain, vomiting, failure to pass meconium, abdominal distension, perforation, mass or for suspected obstruction. The radiation dose involved in abdominal radiography, although significant, the diagnostic information provided outweighs the risk. Dose reduction techniques should be employed to reduce the radiation dose to infants and children. Spectrum of atresias and stenosis from the esophagus up to the rectum, Hirschsprung disease, small left colon syndrome, and anorectal malformations can be identified with a detailed and systematic contrast study. They act as an adjunct in the diagnosis of conditions such as intussusception and hypertrophic pyloric stenosis. Inflammatory conditions such as acute appendicitis, necrotizing enterocolitis, and acute conditions such as pneumoperitoneum are also well appreciated on plain abdominal radiographs.
Keywords: plain radiograph; abdomen; pediatric; intestinal obstruction; pneumoperitoneum